BEHAVIOR OF RAT NEONATES WITH INHERITED STRESS-INDUCED ARTERIAL HYPERTENSION - I. O. Meshkov; T. A. Alekhina; T. A. Moreva (Вавиловский журнал генетики и селекции)
The present work concerns the development of locomotor activity, rates of weight gain, vibrissa growth, and time of eyelid opening in two inbred rate strains in the early development. The strains were: rats with inherited stress-induced arterial hypertension (ISIAH) and Wistar Albino Glaxo (WAG) rats as control. Different dynamics of weight gain and vibrissae growth were shown. However, the strains did not differ in the rate of hair growth and time of eyelid openings. Pups of the ISIAH strain exhibited a delay in behavioral maturation in the first week of postnatal development compared to WAG pups of the same age and showed higher locomotor activity in the second week. Differences in behavior between ISIAH and WAG strains in the open field test in the third week revealed higher levels of exploratory behavior and adaptability of ISIAH pups in the novel environment than in WAG pups. Thus, pups of the ISIAH and WAG strains differed significantly in indices of motor development within the first three weeks of postnatal development but not in vibrissa growth, hair coat formation, or eye opening by the end of the 2nd week.